8
$\begingroup$

So I am trying to show the following: $$\sum_{n \leq x} \frac{\mu(n)}{n} \log{\frac{x}{n}}=O(1) $$ so I tried partial summation as following:

Let $A(x)=\sum_{n \leq x} \frac{\mu(n)}{n}$, then we have $$\sum_{n \leq x} \frac{\mu(n)}{n} \log{\frac{x}{n}}= \int_1^{x} \frac{A(t)\mathrm dt}{t},$$ and $A(t)$ is clearly very small, or $o(1)$ for all $t \in [1,x]$. My question is how to go from here to conclude that the error term is $O(1)$?

$\endgroup$
8
  • 1
    $\begingroup$ For what it's worth, I showed $\sum_{n \leq x} \frac{\mu(n)}{n} \log{\frac{x}{n}}=O(1)$, using generalized Möbius inversion, as part of my answer to a previous question of yours. $\endgroup$ Sep 29, 2011 at 3:13
  • $\begingroup$ If you go the partial summation route, you will need an estimate of $A(t)$ that's more precise than $o(1)$ to conclude the $O(1)$ result you want at the end. For example, if $A(t) = \frac{1}{1+ \log t}$, then $$\int_1^{x} \frac{A(t) dt}{t} = \left.\log (1+\log t)\right|_1^x =\log (1+\log x),$$ which is not $O(1)$. $\endgroup$ Sep 29, 2011 at 3:30
  • $\begingroup$ So I think in your answer, there is a error:$$\sum_{n \leq x} \frac{1}{n}=\log{x}+\gamma+O(\frac{1}{x})$$, thus when use Generalized Mobius inversion, we have $$\sum_{n \leq x} \frac{\mu(n)}{n} \log{\frac{x}{n}}=-\sum_{n \leq x} \frac{\mu(n)}{n}\gamma-\sum_{n \leq x} \mu(n) O(\frac{1}{x})+1=-o(1)-\sum_{n \leq x} \mu(n) O(\frac{1}{x})+1$$, However, the middle part doesn't seems to be O(1). $\endgroup$
    – Rob
    Sep 29, 2011 at 5:56
  • 1
    $\begingroup$ I've corrected the mistake in my other answer. $\endgroup$ Sep 29, 2011 at 13:13
  • 1
    $\begingroup$ Sure. Anything that is $o(1)$ is also $O(1)$, and so you have $O(1) + O(1) + O(1) = O(1)$. $\endgroup$ Sep 30, 2011 at 0:16

1 Answer 1

6
$\begingroup$

As you mentioned, we have $$\sum_{n\leq x}\frac{\mu(n)}{n} \log\frac{x}{n}=\int_1^x \left(\sum_{m\leq t}\frac{\mu(m)}{m}\right) \frac{dt}{t}.$$

You need a particular bound on the inner sum. For instance, since $\sum_{m\leq t}\frac{\mu(m)}{m}\ll (\log t)^{-2}$, the result follows.

Here is cool trick however. Notice that $$\sum_{nd\leq x}\frac{\mu(n)}{nd}=\sum_{k\leq x}\frac{1}{k}\sum_{d|k}\mu(d)=1.$$ Now, write the first sum as $$\sum_{n\leq x}\frac{\mu(n)}{n}\sum_{k\leq\frac{x}{n}}\frac{1}{k}=\sum_{n\leq x}\frac{\mu(n)}{n}\left(\log\left(\frac{x}{n}\right)+\gamma+O\left(\frac{n}{x}\right)\right).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.